2001
DOI: 10.1161/hc3501.095485
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calcium, Inorganic Phosphate, and pH on Isometric Force in Single Skinned Cardiomyocytes From Donor and Failing Human Hearts

Abstract: Background-During ischemia, the intracellular calcium and inorganic phosphate (P i ) concentrations rise and pH falls. We investigated the effects of these changes on force development in donor and failing human hearts to determine if altered contractile protein composition during heart failure changes the myocardial response to Ca 2ϩ , P i , and pH. Methods and Results-Isometric force was studied in mechanically isolated Triton-skinned single myocytes from left ventricular myocardium. Force declined with adde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
84
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 30 publications
9
84
1
Order By: Relevance
“…For example, separate studies using epicardial biopsies [10] and samples from unspecified regions of the heart [11] have shown that isometric force is reduced by ~80% in patients with heart failure. Other works, using samples from unspecified regions of the left ventricle, suggests that there is no significant effect of heart failure on maximum isometric force [12][13][14]. In the present experiments, heart failure reduced the average force generated by the experimental preparations (Figure 2, p=0.042).…”
Section: Region-specific Modifications In Systolic Functionsupporting
confidence: 46%
“…For example, separate studies using epicardial biopsies [10] and samples from unspecified regions of the heart [11] have shown that isometric force is reduced by ~80% in patients with heart failure. Other works, using samples from unspecified regions of the left ventricle, suggests that there is no significant effect of heart failure on maximum isometric force [12][13][14]. In the present experiments, heart failure reduced the average force generated by the experimental preparations (Figure 2, p=0.042).…”
Section: Region-specific Modifications In Systolic Functionsupporting
confidence: 46%
“…We have previously shown that this results in excellent tissue preservation (Figure 5B in Freiburg et al), 19 whereas others 3,21 have shown that active and passive mechanical properties are well maintained in freeze-thawed samples. Muscle strips were dissected from LV specimens, skinned overnight at 4°C in relaxing solution containing 1% vol/vol Triton X-100, and then washed thoroughly with relaxing solution.…”
Section: Muscle Mechanicsmentioning
confidence: 82%
“…The elimination of the higher Ca 2+ sensitivity of force production by 10 mM P i in the failing myocytes occurred both at pH 7.2 and at pH 6.5, in perfect agreement with the notion that the P i effect is independent from that of protons. 24,27 …”
Section: Discussionmentioning
confidence: 99%
“…27 During physiological cardiac activity, the thin filaments are far from Ca 2+ saturation. Differences in the mechanical parameters of failing and non-failing hearts at intermediate [Ca 2+ ] therefore bear important functional consequences for the cardiac performance.…”
Section: Functional Implicationsmentioning
confidence: 99%